The Ghetto, and Other Poems: An Annotated Edition. - Ridge, Lola (Fordham University Press : Fordham University Press, 2023)
At last recovered in this enriching annotated edition, this important but neglected work of American modernism offers a unique poetic encounter with the Jewish communities in New York's Lower East Side.